Project-Based Learning Role Analysis to Improve Student’s Writing Skills in Elementary School - Widhiastuti, Kingkin; Permatasari, Adelia Putri; Khoiroh, Makrifatul; Aini, Muntaza Nur; Kusumaningrum, Shirly Rizki (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
The purpose of this research activity is to describe the role of the Project Based Learning model in writing skills in fourth-grade elementary school students. The method used in this research is a research method. descriptive qualitative. The place for this research is SDN 2 Girimoyo Karangploso, Malang. Class IV students totaling 25 people and class IV teachers at SDN 2 Girimoyo Karangploso are the subjects in this study. Documentation, observation, and interviews are techniques that will be used as data collection techniques. Data analysis techniques in this study are the stages of data reduction, data presentation, and data verification. The results of this study indicate that the learning process using Project Based Learning is more efficient in students’ writing skills than learning using the lecture method and the use of teaching materials in the form of learning books. Where learning activities using the Project model. Based Learning is able to make students play an active role in learning activities, students are better able to express ideas about what they want to write on the given sheet, namely the vegetable planting documentation sheet.